Getting started with Kubernetes - Vugt, Sander van (LiveLessons (Indianapolis, Ind.), 2018)
"Getting Started with Kubernetes LiveLessons offers a complete overview of all that is needed to start working with Kubernetes. It starts by explaining why Kubernetes is needed, and how it is used to orchestrate containers. During the course, a lab environment is built using Minikube, thus allowing anyone to create a Kubernetes test environment. Through lesson labs, demos, and whiteboard demonstrations, the course covers advanced topics, such as creating services, exposing Kubernetes Pods to external users, and integrating Kubernetes into public cloud offerings. It also provides an introduction to working with the API."--Resource description page